2004
DOI: 10.1021/jo048592h
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic C−H...O Interactions in a Series of Bindone Analogues. NMR and Quantum Mechanical Study

Abstract: The aromatic C-H...O hydrogen bonding within the series of the structurally relative indenone derivatives has been studied. The presence of the hydrogen bonds is corroborated by the large low-field chemical shifts of the protons involved in the hydrogen bond observed experimentally and reproduced by quantum mechanical calculations. Further confirmation is provided by analysis of the orbital overlap coefficients, (13)C NMR chemical shifts, and one-bond spin-spin coupling constants J((13)C-(1)H). The relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…1) (23, 66 -69); thus, we sought to verify our experimental chemical shift change using quantum chemistry calculations. Although this combination of techniques has been used to identify CH⅐⅐⅐O hydrogen bonds in small organic molecules (37,70,71) and in computational biology (68), it has, to our knowledge, not yet been applied experimentally in biological macromolecules. Using this combination of techniques, we reasoned that it should be possible to solve for the hydrogen positions and, thus hydrogen bonding patterns, of the AdoMet methyl group within the SET7/9 active site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) (23, 66 -69); thus, we sought to verify our experimental chemical shift change using quantum chemistry calculations. Although this combination of techniques has been used to identify CH⅐⅐⅐O hydrogen bonds in small organic molecules (37,70,71) and in computational biology (68), it has, to our knowledge, not yet been applied experimentally in biological macromolecules. Using this combination of techniques, we reasoned that it should be possible to solve for the hydrogen positions and, thus hydrogen bonding patterns, of the AdoMet methyl group within the SET7/9 active site.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of CH⅐⅐⅐O hydrogen bonding in small organic molecules showed that the chemical shift calculations of hydrogen were usually accurate to 0.1 ppm of the experiment (37,70,71). Error in biological molecules could arise from many sources, including but not limited to implicit solvation modeling and large or truncated molecules used in calculations.…”
Section: Resultsmentioning
confidence: 99%
“…[18] However, the hydrogens at the sp 2 carbon atoms in anions 2a and 3a meet the above-mentioned criteria [20] and are hydrogen bonded. This is supported by an increase in the respective one-bond coupling constants 1 J( 13 C, 1 H) from 164.1 Hz for C-2 in 1a to 172.7 Hz for C-11 in 2a, and to 177.5 Hz for C-11 in 3a ( Table 1).…”
Section: Intramolecular Aromatic C-h···o Bonding In 2a-4amentioning
confidence: 99%
“…Recently, we demonstrated [18] that the geometry of the C-H···O=C fragments of derivatives 2-4 meet the criteria, which set the limits for possible C-H···O hydrogen bonding occurrence. [20] A detailed NMR spectroscopic and quantum mechanical study revealed the following manifestations of hydrogen bonding: (1) large low-field chemical shifts of the protons and carbon atoms involved, (2) increase in the onebond ( 13 C, 1 H) spin-spin coupling constants, and (3) non-zero positive values of the overlap coefficients between the orbitals involving the interacting oxygen and hydrogen atoms.…”
Section: Intramolecular Aromatic C-h···o Bonding In 2a-4amentioning
confidence: 99%
See 1 more Smart Citation